2022
DOI: 10.3390/ijms23020664
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Role of Pituitary Adenylate Cyclase-Activating Polypeptide for Dry Eye Disease

Abstract: Dry eye disease (DED) is caused by a reduction in the volume or quality of tears. The prevalence of DED is estimated to be 100 million in the developed world. As aging is a risk factor for DED, the prevalence of DED is expected to grow at a rapid pace in aging populations, thus creating an increased need for new therapies. This review summarizes DED medications currently in clinical use. Most current medications for DED focus on stimulating tear secretion, mucin secretion, or suppressing inflammation, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Previous in vivo studies have confirmed that PACAP38, when administered as eye drops, can permeate ocular barriers and exhibit retinoprotective effects [76]. Additionally, PACAP38 has been identified as a new candidate medication for Dry Eye Disease [77]. A study suggests that VIP and PACAP analogs, explicitly developed for therapeutic purposes, can modulate molecular and cellular processes relevant to treating high-risk neuroblastoma [78].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo studies have confirmed that PACAP38, when administered as eye drops, can permeate ocular barriers and exhibit retinoprotective effects [76]. Additionally, PACAP38 has been identified as a new candidate medication for Dry Eye Disease [77]. A study suggests that VIP and PACAP analogs, explicitly developed for therapeutic purposes, can modulate molecular and cellular processes relevant to treating high-risk neuroblastoma [78].…”
Section: Discussionmentioning
confidence: 99%
“…For animal ethical reasons and to achieve the most accurate dosing possible, repeated needle administration was not used in our study, and we developed a cannulation method similar to Larsen and Christensen [54]. As the local administration of PACAP showed protective effects in a model of dry eye disease and in neurological animal models, local use is a preferred mode of treatment [55]. For instance, local administration of PACAP-38 has neuroprotective effects in animal models of ischemic stroke, traumatic brain injury, and Parkinson's disease [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Newer drugs, such as IL-1 receptor antagonists, serine protease inhibitors, resolvin analogues, and integrin antagonists, are under research [96]. The therapeutic role of pituitary adenylate cyclase-activating polypeptide is also being explored, and drug delivery systems, such as liposomal rebamipide, are being considered [97,98].…”
Section: Future Researchmentioning
confidence: 99%